1995
DOI: 10.1007/bf02785411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aluminum chloride on the kinetics of rat cortex synaptosomal ATP diphosphohydrolase 9EC 3.6.1.5)

Abstract: Aluminum chloride (AlCl3), a neurotoxic compound, inhibited ATP diphosphohydrolase activity of synaptosomes obtained from cerebral cortex of adult rats. The metal ion significantly inhibited ATPase and ADPase activities of the enzyme at all concentrations tested in vitro (0.01, 0.05, 0.5, 5, and 10 mM) in the presence of 1.5 mM calcium. When tested in the absence of Ca2+, and with increasing amounts of Al3+, enzyme activity remained below basal levels, suggesting that the trivalent cation Al3+ is not a substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
6
1
1
Order By: Relevance
“…Thus, as NTPDase and 5′‐nucleotidase enzymes are activated by Ca +2 or Mg 2+ cations, any alteration in the availability of ions affects the activities of these enzymes. Schetinger et al (1995), observed a competitive inhibition between aluminium and calcium, suggesting that the aluminium ion forms complexes with ATP and ADP, since these complexes are not hydrolyzed by nucleotidases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, as NTPDase and 5′‐nucleotidase enzymes are activated by Ca +2 or Mg 2+ cations, any alteration in the availability of ions affects the activities of these enzymes. Schetinger et al (1995), observed a competitive inhibition between aluminium and calcium, suggesting that the aluminium ion forms complexes with ATP and ADP, since these complexes are not hydrolyzed by nucleotidases.…”
Section: Discussionmentioning
confidence: 99%
“…NTPDase hydrolyzes the extracellular nucleoside tri and diphosphate in the presence of Ca 2+ or Mg 2+ , as it is activated by these cations (Zimmermann et al, 1998). Nucleotide hydrolysis may be impaired by Al, probably because it interferes in the homeostasis of divalent cations (Schetinger et al, 1995; Moretto et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A competitive inhibition between aluminium and Ca 2+ was suggested as the primary mechanism responsible for the inhibitory effect of aluminium on apyrase (EC 3.6.1.5; ecto-ATPDase) activity. Schetinger et al [241] observed that AlCl 3 inhibits both the ATPase and ADPase activities of synaptosomes isolated from rat cerebral cortex, with an estimated IC 50 value of 5.0 mM in the presence of 1.5 mM CaCl 2 . Here the enzyme activity remained below basal levels in the absence of Ca 2+ .…”
Section: Inactivation Of Neurotransmittersmentioning
confidence: 98%
“…However, recent data have raised serious questions about the hazards of this metal (1,2). Aluminum salts administered by different routes can produce toxic effects in animal models (3)(4)(5) some of which involve alterations in enzymatic activities (6,7). It is presently accepted that aluminum intoxication may induce anemia and encephalopathy in humans and animals (8).…”
Section: Introductionmentioning
confidence: 99%